„Słodki kotek” a kultura polska. Rozważania wokół książki Magdaleny Kamińskiej Memosfera. Wstęp do cyberkulturoznawstwa - Wójtowicz, Ewa (Człowiek i Społeczeństwo, 2017)
In the new book Memosphere. Introduction to Cybercultural Studies (2017) Magdalena Kamińska publishes the result of her long-term studies on Internet-based culture and its components, such as netlore, lolcontent, memes and more. The book is focused on Polish cybercultural phenomena revealing their particularly local aspects, as well as pointing at the position of Polish cyberculture in the broader media landscape. Memosphere is comprised of a series of case studies, each developed thoroughly and discussed from various perspectives, such as netnography. The framework of the book is based on so-called rich points (after Michael H. Agar), chosen by Magdalena Kamińska in the attempt to find the most inspiring examples, including: various memes native to Polish culture, the Polish version of cyber-(n)ostalgy, the case of iuxtabrities (social-media bound cewebrities) or a circulation of counter knowledge. Some of the issues discussed in Memosphere have also been present in the realm of post-Internet art and examined by international researchers (O. Lialina, A.X. Mina, D. Quaranta) which proves their universal character within the global cyberculture. One of the most influential features of memes (after E. Zuckerberg) is an image of a cat (funny or cute), enabling the circulation of important, even serious or activist content. From digital naives, to digital natives, all the members of cyberculture become transmitters of memes and the prosumers of digital folklore. Also, Kamińska introduces her own proposal of the new methodology of cybercultural studies based on cultural studies as well as anthropology. The book proves that a demand for the branch of culture studies aimed at such a dynamic field of studies as cyberculture, is pivotal for the future development of cultural studies as an academic discipline. Ewa Wójtowicz, „Słodki kotek” a kultura polska. Rozważania wokół książki Magdaleny Kamińskiej Memosfera. Wstęp do cyberkulturoznawstwa [„Sweet kitten” and Polish culture. Reflections around the book of Magdalena Kamińska Memosphere. Introduction to cyber cultural studies], edited by W. Bryl-Roman, „Człowiek i Społeczeństwo” vol. XLIII: Projektowanie w latach 70. [Designing in the 1970s], Poznań 2017, pp. 193-201, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271.